Menguji Kepuasan Hubungan Melalui Intimasi dan Perasaan Cemburu pada Pelaku Hubungan Friends with Benefits - Putu Yunita Trisna Dewi; M. Arief Sumantri (Jurnal Psikologi Teori dan Terapan, 2020)
Friends with Benefits (FWB) is a friendship of the opposite sex that involves sexual activity without commitment, feelings of love and encouragement to continue the relationship toward a romantic relationship. This study aims to determine the role of intimacy and jealousy towards the relationship satisfaction of individuals undergoing the FWB and the role of jealousy towards intimacy, and describing the emotions and views of participants on their FWB relationships. The subjects were 304 people undergoing FWB relationship in the last two years. Data were collected using Miller Social Intimacy, Multidimensional Jealousy, and Relationship Assessment Scales. Hierarchical linear regression and descriptive analysis were used to analyze data. Participants experiences of their FBW relationship were also collected and analyzed qualitatively. The result showed that intimacy and jealousy significantly predicted the relationship satisfaction both simultaneously and partially. Jealousy also significantly influences intimacy. A qualitative analysis reveals three categories that describe the emotions and views of the participants towards their FWB  relationships, namely feeling satisfied and happy, feeling less satisfied and regretful, and feeling happy but regretful.Keywords : friends with benefits, intimacy, jealousy, relationship satisfaction. Abstrak: Friends with Benefits (FWB) adalah hubungan pertemanan lawan jenis yang melibatkan hubungan seksual tanpa komitmen, perasaan cinta dan dorongan untuk melanjutkan ke hubungan yang romantis. Penelitian ini bertujuan untuk menguji peranan intimasi dan perasaan cemburu terhadap kepuasan hubungan partisipan yang menjalani hubungan FWB, peranan perasaan cemburu terhadap intimasi, serta mendeskripsikan gambaran emosi dan pandangan partisipan saat menjalani hubungan FWB. Partisipan penelitian berjumlah 304 partisipan, yang menjalani hubungan FWB dalam kurun waktu dua tahun terakhir. Data dikumpulkan dengan skala Miller Social Intimacy, Multi-dimensional Jealousy, dan Relationship Assesment. Data dianalisis menggunakan regresi linier berjenjang. Data kualitatif juga dikumpulkan dan dianalisis secara deskriptif untuk mendalami perasaan dan pandangan partisipan terhadap FWB yang dijalani. Hasil penelitian menunjukkan intimasi dan perasaan cemburu secara signifikan mempengaruhi kepuasan hubungan baik secara simultan maupun parsial. Perasaan cemburu juga secara signifikan memberi pengaruh terhadap intimasi. Secara kualitatif, ditemukan tiga kategori yang menggambarkan emosi dan pandangan partisipan dalam menjalani hubungan FWB, yaitu merasa puas dan senang, kurang puas hingga menyesal, dan merasa senang namun ada penyesalan.